Management of Fatigue in Post-Stroke Patients - Ni Luh Putu Thrisna Dewi; Anak Agung Sri Sanjiwani; Ni Made Nopita Wati; Ketut Lisnawati (KHD Production, 2023)
Post-stroke patients often have sequelae that are difficult to avoid. One of the impacts that can occur after a stroke is the onset of cognitive impairment, physical disability, and even death due to the extent of brain damage that occurs. Another impact of stroke is Fatigue Post Stroke (FPS), where most stroke patients experience fatigue, and this condition can persist even though other symptoms caused by stroke have improved. This literature review aims to determine the appropriate management of fatigue after a stroke. The method in this study is a literature review by collecting published literature from databases such as ResearchGate, Google Scholar, and PLOS using Boolean stroke management and post-stroke fatigue. The literature search focused on articles related to fatigue in stroke patients. Both used RCT (Randomized Control Trial) design, Quasi Experiment, Qualitative study, and Survey study from the year (2015-2022). Based on the results of data extraction from the author, two themes can be taken by the author, post-stroke patients who experience fatigue and fatigue management in stroke. The update in this literature review is the manifestation of fatigue conditions that, on average, will be experienced by stroke patients. If not handled properly, it will have a worse impact physically and psychologically, which can certainly interfere with the recovery process. So, it is necessary to appropriately manage both physical exercise and psychological interventions following the fatigue conditions of post-stroke patients. We recommend that in health services, nurses pay more attention to patient responses related to fatigue to provide appropriate nursing interventions and increase patients' desire to undergo rehabilitation.